Enhancing occupational safety in the X-ray laboratory. Issue 4 (12th August 2021) - Bansal, Priya; Luna, Michael; Dutton, Margaret; Maini, Aneel; Banerjee, Subhash; Brilakis, Emmanouil S.; Maini, Brijeshwar; Khalili, Houman
Abstract : Despite more than 80% of interventional operators reporting one or more orthopedic injuries attributed to the X-ray laboratory, there has been limited adoption of various strategies and equipment to minimize these injuries. A comprehensive review of these methods to reduce musculoskeletal strain is lacking in the current literature, and is essential in order to ensure a long, healthy, and productive interventional career.